2021
DOI: 10.3389/fpsyt.2021.772081
|View full text |Cite
|
Sign up to set email alerts
|

Neural Changes in Borderline Personality Disorder After Dialectical Behavior Therapy–A Review

Abstract: The biological component of the biosocial theory of emotion regulation stipulates that borderline personality disorder (BPD) arises from biological vulnerabilities to heightened emotional reactivity. Comprehensive reviews have consistently implicated abnormalities in the amygdala, anterior cingulate cortex, and hippocampus in the neurobiology of BPD. While Dialectical Behavior Therapy (DBT) is the leading evidence-based psychotherapy for the treatment of BPD, there remains a paucity of literature examining cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…In addition to this, Mancke et al [ 9 ] found an increased grey matter volume in cortical regions connected with emotion regulation in women with BPD after receiving DBT treatment. These findings are supported by the review conducted by Iskric and Barkley-Levenson [ 10 ]. However, current published findings on the neural correlates of DBT effects are still scarce and much further research is needed to draw definitive conclusions.…”
Section: Introductionsupporting
confidence: 81%
“…In addition to this, Mancke et al [ 9 ] found an increased grey matter volume in cortical regions connected with emotion regulation in women with BPD after receiving DBT treatment. These findings are supported by the review conducted by Iskric and Barkley-Levenson [ 10 ]. However, current published findings on the neural correlates of DBT effects are still scarce and much further research is needed to draw definitive conclusions.…”
Section: Introductionsupporting
confidence: 81%
“…Emotion dysregulation is a core symptom of BPD [55], and DBT focuses on this dysregulation by training patients to differentiate their emotions [3]. Functional neuroimaging studies of such emotion dysregulation in patients with BPD have used univariate analyses to consistently reveal altered activation levels of the amygdala in patients with BPD [56, 57], also with respect to treatment programs incorporating DBT [58]. However, the use of multivariate pattern analysis opens up new avenues for interpreting the role of the amygdala in BPD, as representational similarity analysis (RSA) allows one to hypothesize not only about the involvement of a brain region but more specifically about the representational content underlying its activity patterns [59].…”
Section: Discussionmentioning
confidence: 99%
“…As this study is the first to apply RSA to fMRI data of patients with BPD, follow-up work incoporating similar methodology, larger samples, and additional questionnaires (e.g., the Difficulties in Emotion Regulation Scale [68, 69]) is warranted in order to better characterize the relationship between neural representational spaces, emotion dysregulation, and BPD. One idea would involve carrying out several neuroimaging scans throughout the course of a DBT program in conjunction with a dismantling design [58]. This approach could help to constrain our understanding of the relationship between specific aspects of therapy and changes in the neural representational geometry, potentially revealing how such altered representational spaces map onto pathological behavior in BPD, thereby increasing the prognostic value of functional MRI in the clinic.…”
Section: Limitations and Future Outlookmentioning
confidence: 99%
“…For example, a recent meta-analysis reported functional hyperactivity of the left amygdala during aversive vs. neutral stimuli, as well as smaller gray matter volume of the amygdala in BPD ( Schulze et al, 2016 , 2019 ). This amygdala hyperactivation has been proposed to reflect the deviant salience of negative emotional stimuli and to be remediated by psychotropic medication ( Schulze et al, 2016 ) and psychotherapy ( Iskric and Barkley-Levenson, 2021 ) in BPD. We note that it is unclear whether remediation of amygdala hyperactivity is related to specific treatments or whether it is a general prerequisite for recovery from borderline symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…We note that it is unclear whether remediation of amygdala hyperactivity is related to specific treatments or whether it is a general prerequisite for recovery from borderline symptomatology. Notwithstanding this ambiguity, evidence shows that effects of DBT are also associated with changes in blood oxygen level-dependent (BOLD) signal in the amygdala ( Schnell and Herpertz, 2007 ; Krause-Utz et al, 2014 ; Salvador et al, 2016 ; Iskric and Barkley-Levenson, 2021 ). Here, we build on these previous findings by assessing the hypothesis that BPD is accompanied by abnormalities in aversive PIT and associated BOLD signal in the amygdala.…”
Section: Introductionmentioning
confidence: 99%